PENGARUH LINGKUNGAN KERJA NON-FISIK, GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP LOYALITAS KARYAWAN DI PT TRANS DIGITAL MEDIA - Muhammad Naufal, - (2021)
This research is a quantitative research which aims to determine the effect of the Non-Physical Work Environment, Leadership Style and Work Motivation on employees in the marketing division of PT Trans Digital Media. The sample used is 45 employees of the marketing division using a saturated sample. Data collection is carried out through the distribution of google forms which are distributed to employees in the marketing division. Using ingerential analysis techniques and processing data through IBM SPSS with a significant level of 5% or 0.05. The results of the tests carried out showed that the non-physical work environment variable partially had a significant effect on the employee loyalty variable because it had a t count value greater than the t table value (9.328 < 2.019) and a significance value of 0.001 < 0.05. Meanwhile, the leadership style variable partially and significantly affects employee loyalty because it has a t-count value greater than the t-table value (8.958 > 2.019) and a significance value of 0.001 <0.05. And the work motivation variable partially and significantly influences employee loyalty because it has a t-count value greater than the t-table value (6.571> 2.019) and a significance value of 0.001 <0.05. Meanwhile, simultaneously, non-physical work environment variables, leadership style and work motivation have a significant and significant effect on employee loyalty variables because the calculated f value is greater than f table (8.958 > 2.019) and a significant value is 0.001 < 0.05. The coefficient of determination test was obtained at 0.682 or 68.2% employee loyalty influenced by non-physical work environment, leadership style and work motivation.